2012
DOI: 10.1007/s11063-012-9211-7
|View full text |Cite
|
Sign up to set email alerts
|

Existence and Exponential Stability of Multiple Periodic Solutions for a Multidirectional Associative Memory Neural Network

Abstract: The paper proposes several mathematical models of the multidirectional associative memory (MAM) neural network by analyzing its structure. A model of MAM with distributed delays is studied. Under some new assumptions on activation functions, 2 n 0 [m/2] invariant subsets of MAM are constructed. Then the existence and the exponential stability of 2 n 0 [m/2] periodic solutions located on invariant subsets are obtained by constructing a suitable Liapunov function and a Poincaré mapping. An estimating method of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Remark 2. In the earlier papers, a series of results on the multiperiodicity for neural networks with continuous neuron activation functions were obtained [10,[17][18][19]. However, for neural networks with discontinuous neuron activation functions, there are few papers consider the multiperiodicity of them.…”
Section: Multi-periodicitymentioning
confidence: 99%
See 2 more Smart Citations
“…Remark 2. In the earlier papers, a series of results on the multiperiodicity for neural networks with continuous neuron activation functions were obtained [10,[17][18][19]. However, for neural networks with discontinuous neuron activation functions, there are few papers consider the multiperiodicity of them.…”
Section: Multi-periodicitymentioning
confidence: 99%
“…Therefore, the methods used in the papers [10,[17][18][19] cannot be applied to discuss the existence of multiple periodic solutions to the system (4.2). To deal with the existence of multiple periodic solutions (or equilibrium) of neural networks systems with general discontinuous neuron activations functions, the methods in this paper are very effective and thus the results of this paper (Theorems 3.3 and 3.4) are essentially new.…”
Section: > < >mentioning
confidence: 99%
See 1 more Smart Citation
“…So it is necessary that there exist multiple stable equilibria or periodic orbits for neural networks, which are usually referred to as multistability or multiperiodicity, respectively. In the last few years, the multistability and multiperiodicity of neural networks have been reported in [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] and the references therein. In particular, [14][15][16][17][18][19][20][21] investigated the multistability or multiperiodicity of neural networks with sigmoidal activation functions or nondecreasing saturated activation functions.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of Hopfield neural networks and BAM neural networks is discussed in a lot of recently published literature works [8][9][10][11][12], but the researchers about MAM neural networks are mainly focused on learning algorithms, fault tolerance, and retrieval efficiency of MAM neural networks [3][4][5][6]. To the best of our knowledge, the research on the theory of MAM neural networks was reported only in a few papers [13][14][15][16][17][18]. Chen et al proved the stability of some specific types of MAM neural networks in [13,14].…”
Section: Introductionmentioning
confidence: 99%